(untitled) (REMUNOM, 2025)
Pasture degradation is one of the main challenges for the sustainability of the Brazilian agricultural sector, with serious economic, social, and environmental consequences. This study presents a review of the causes, impacts, and strategies for the recovery of degraded pastures. The main causes include inadequate management, overgrazing, poor formation, and lack of fertilization, resulting in soil compaction, erosion, and biodiversity loss. The consequences encompass reduced agricultural productivity, increased production costs, uncontrolled agricultural expansion, and social impacts on rural communities. From an environmental perspective, degradation compromises soil quality, water resources, and ecosystem services, as well as contributing to climate change. To mitigate these impacts, several strategies have been proposed, such as the Crop-Livestock-Forest Integration (ILPF), rotational pasture management, the introduction of adapted forage species, and the recovery of soil fertility through liming and fertilization practices. The adoption of monitoring technologies, such as remote sensing, also stands out for its efficiency in identifying degraded areas. Public policies that encourage sustainable practices and offer technical assistance and rural credit are essential for large-scale pasture recovery. Recovering and ensuring the sustainability of pastures represents not only an opportunity to preserve the environment but also to increase agricultural productivity and promote competitiveness in the global market. In conclusion, an integrated approach is essential to ensure the economic, social, and environmental viability of the Brazilian agricultural sector.